Literature Review: Peran Empati dalam Pengelolaan Stres Pada Remaja di Indonesia - Yesania Putri Umbu Deta; Ananda Maulana Putra Sanjaya; Arif Rachman; Sofiana Sofiana (Pelantar Press, 2026)
Stress among adolescents is an increasing mental health concern and is influenced by various psychosocial factors. Empathy, defined as the affective ability to understand and share others’ emotions, is believed to play an important role in helping adolescents manage stress adaptively. This study aims to examine the role of empathy in stress management among adolescents in Indonesia through a literature review. The method used was a narrative literature review by searching open-access scientific articles through PubMed, Google Scholar, and ResearchGate published between 2021 and 2025, using the keywords empathy, stress, stress management, adolescent, and Indonesia. Approximately 12,000 articles were identified in the initial search. After applying inclusion and exclusion criteria, 10 relevant articles were selected for analysis. The findings indicate that empathy contributes to adolescent stress management through mechanisms such as emotional regulation, enhanced resilience, and strengthened peer social support. Adaptive empathy is associated with better coping abilities and lower stress levels, whereas empathy that is not accompanied by adequate emotional regulation may increase vulnerability to stress. In conclusion, empathy is an important component in adolescent stress management and has potential implications for the development of promotive and preventive mental health interventions for adolescents